Immune-Related Adverse Events Associated with Anti-PD-1/PD-L1 Treatment for Malignancies: A Meta-Analysis - Wang, Peng-Fei; Chen, Yang; Song, Si-Ying; Wang, Ting-Jian; Ji, Wen-Jun; Li, Shou-Wei; Liu, Ning; Yan, Chang-Xiang (Frontiers in Pharmacology, 2017)
Background: Treatment of cancers with programmed cell death protein 1 (PD-1) pathway inhibitors can lead to immune-related adverse events (irAEs), which could be serious and even fetal. Therefore, clinicians should be aware of the characteristics of irAEs associated with the use of such drugs. Methods: The MEDLINE, EMBASE, and Cochrane databases were searched to find potential studies using the following strategies: anti-PD-1/PD-L1 treatment; irAEs; and cancer. R© package Meta was used to pool incidence. Results: Forty-six studies representing 12,808 oncologic patients treated with anti-PD-1/PD-L1 agents were included in the meta-analysis. The anti-PD-1/PD-L1 agents included nivolumab, pembrolizumab, atezolizumab, durvalumab, avelumab, and BMS-936559. The tumor types were melanomas, Hodgkin lymphomas, urothelial carcinomas, breast cancers, non-small cell lung cancers, renal cell carcinomas, colorectal cancers, and others. We described irAEs according to organ systems, namely, the skin (pruritus, rash, maculopapular rash, vitiligo, and dermatitis), endocrine system (hypothyroidism, hyperthyroidism, hypophysitis, thyroiditis, and adrenal insufficiency), digestive system (colitis, diarrhea, pancreatitis, and increased AST/ALT/bilirubin), respiratory system (pneumonitis, lung infiltration, and interstitial lung disease), and urinary system (increased creatinine, nephritis, and renal failure). In patients treated with the PD-1 signaling inhibitors, the overall incidence of irAEs was 26.82% (95 % CI, 21.73–32.61; I2, 92.80) in any grade and 6.10% (95 % CI, 4.85–7.64; I2, 52.00) in severe grade, respectively. The development of irAEs was unrelated to the dose of anti-PD-1/PD-L1 agents. The incidence of particular irAEs varied when different cancers were treated with different drugs. The incidence of death due to irAEs was around 0.17%. Conclusion: The occurrence of irAEs was organ-specific and related to drug and tumor types.